Japanese consumer preferences for additive-free wine labeling - Satoko Kubota; Hirotsugu Sawano; Hiroichi Kono (Agricultural and Food Economics, 2017)
Consumers have recently become more concerned about food additives and food safety. Since its first meeting on September 17, 2003, the Risk Communication Expert Committee has studied and discussed the ideal methods to communicate risk related to food safety issues in response to a Food Safety Commission request. However, there are only a few case studies that actually apply to risk communications. This study aims to analyze consumer preferences for antioxidant-free wine and suggest a tool for risk communications. The study uses a two-stage method: in the first, the analysis identified different types of consumers according to their views of antioxidant-free labels using structural equation model (SEM) analysis; the second stage incorporated the consumer attributes identified by the SEM into a conjoint analysis to calculate willingness to pay (WTP) for each attribute. The WTP results show that the antioxidant-free label has a significant influence on consumer preferences. Notably, consumers who recognize food additive dangers placed significant additional value on wine without antioxidants. On the other hand, consumers who have knowledge of wine and food processing tended to view antioxidant-free wine as low in quality compared to wines made with the original manufacturing process. These results indicate that "adverse selection" has occurred in the wine market in Japan. The results suggest significant differences between consumer groups in terms of awareness of the dangers of food additives and knowledge of wine and food processing. This implies that some consumers are sensitive to food additives. Our research can help regulators create effective means to communication risk related to food additives. In addition, this implies that government guidelines related to wine labels are important, so that Japanese wine may approach international level quality.
Keywords: 330; Antioxidant-free wine; Conjoint analysis; Food safety; Risk communication; Structural equation models